Impacts of prime-age adult mortality on labour supply: Evidence from adolescents and women in South Africa - Yamauchi, Futoshi; Buthelezi, Thabani; Velia, Myriam (Wiley, 2008)
This paper examines the impact of prime‐age adult mortality on the transition made by adolescents from school to the labour market and on female adult labour force participation decisions in South Africa. We find, first, that deaths of prime‐age adults significantly increase both male and female adolescents’ labour force participation as they stop their schooling. Secondly, the death of prime‐age adults in general also decreases school enrolment ex ante. Thirdly, female adults tend to join the labour force following the death of prime‐age adult males. These findings imply that prime‐age adult mortality increases labour supply and disrupts human capital formation.